Seeking Justice on Social Media for Femicides in Türkiye - Özlem Özdemir; Elif Başak Sarıoğlu (Etkileşim, 2024)
Social media platforms have become powerful tools for advocating rights and pursuing justice by mobilizing virtual “crowds”. In Türkiye, where confidence in the justice system has declined, social media has emerged as an alternative means to seek justice. Social media activism is frequently employed in response to femicides, encompassing various communication and legal aspects. This article aims to investigate how social media is utilized in the fight against femicide in Türkiye. Does seeking justice through social media truly influence court decisions? Do users adhere to democratic principles and freedom of expression while engaging in social media activism? What are the positive and negative effects? Additionally, what legal challenges arise from the use of social media? These are the questions explored in this study. Instances such as the release of perpetrators of violence against women, protracted legal processes, or defendants benefiting from lenient sentences deeply disturb public conscience, erode confidence in the justice system, and propel social media activism, which spreads rapidly among the masses. To examine the legal aspects of the issue, in-depth interviews were conducted with fifteen lawyers. The findings reveal that social media posts seeking justice for femicides have a significant impact on large audiences. The study demonstrates that social media serves as a mechanism of social pressure accelerating the process of justice and plays a crucial role in the pursuit of justice. Nevertheless, it also highlights the potential legal risks associated with social media activism.